Publishing and Medicine: A Potentially Integrated Field? - Fan MANG (Wolters Kluwer Health/LWW, 2023)
This article focuses on the intersection of English-language scholarship between the history of publishing and the history of medicine in Imperial China. As an important part of cultural and social history, both topics have attracted attention from a number of historians. This article contains three sections. The first section introduces the evolution of Chinese book and publishing history in recent years and examines what book historians have done in relation to traditional Chinese medicine. The second section explores how medical historians have considered the role of printing in the history of Chinese medicine and the ways in which medical publications were used as primary sources or subjects of research. The third section explores scholarship on medical epistemic genres, a subfield of medical history, in Chinese medicine, specifically focusing on medical case histories and recipes from the comparative and cross-cultural perspectives. Finally, the conclusion explores potential future directions from the integration of Chinese publishing history and medical history.